CONTRIBUŢII PRIVIND ANALIZA EXPLORATORIE A DATELOR TOPOGRAFICE ÎN CERCETAREA ARHEOLOGICĂ SISTEMATICĂ (PANGEEA, 2025)
In the current state of archaeological research, each GIS project is a unique case, according to the purpose of the research, the used methods and techniques, the nature and complexity of the archaeological site, the requirements of the archaeologist. Thus, working methods and the exploitation of a GIS system in archaeology are not standardized. Therefore, many times, correlating the information which is of interest for the specialist, on wider spaces (starting from regional level until the European space) is hard and difficult to interpret.